Sustainable management of saline and sodic soils for growing vegetable crops - A review - Marimuthu, J; Yasodha, P; Kumar, S; Malini, N; Rajeswari, R; Uma Maheswari, T; Geethalakshmi, Indran; Sabir Ahamed, A; Nithila, S; Jegadeeswari, V; et al. (Plant Science Today, 2025)
Vegetables are essential that play a crucial role in human nutrition. Salinity is a major constraint affecting agricultural productivity globally. Salt affects soils comprise approximately 20 % of cultivated land and 33 % of irrigated land. Salt stress hampers plant growth, thereby reducing the yield and quality of various crops. Salinity and sodicity adversely affect the biological, physical and chemical properties of soil, leading to reduced productivity and land degradation, particularly in irrigated and rainfed agricultural systems. Salinity reduces protein, fatty acid and total carbohydrate content in crops, while often increasing the accumulation of amino acids. The presence of soluble salts and excess sodium ions (Na+) in soil adversely affects plant health, emphasizing the need for effective resource management and sustainable practices. High salinity leads to surface crusting, reduced water infiltration, sodium-induced soil dispersion and decreased hydraulic conductivity (HC), all of which negatively impact plant development. Sodicity refers to the presence of excessive exchangeable sodium in soil relative to calcium and magnesium, which disrupts soil structure and fertility. High sodicity inhibits plant growth due to salt toxicity, nutritional imbalances and reduced availability of essential minerals in the soil. This review discusses the impact of saline and sodic soils on various vegetable crops and explores sustainable management practices to mitigate their effects.